2010
DOI: 10.1084/jem.20092618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human DNGR-1+ BDCA3+ leukocytes as putative equivalents of mouse CD8α+ dendritic cells

Abstract: In mouse, a subset of dendritic cells (DCs) known as CD8α+ DCs has emerged as an important player in the regulation of T cell responses and a promising target in vaccination strategies. However, translation into clinical protocols has been hampered by the failure to identify CD8α+ DCs in humans. Here, we characterize a population of human DCs that expresses DNGR-1 (CLEC9A) and high levels of BDCA3 and resembles mouse CD8α+ DCs in phenotype and function. We describe the presence of such cells in the spleens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
664
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 603 publications
(694 citation statements)
references
References 56 publications
(98 reference statements)
22
664
2
6
Order By: Relevance
“…They expressed IRF8 and TLR3, two hallmarks of this subset in blood and spleen, 22,23 albeit at lower levels than their in vivo DC counterparts. Furthermore, similar to blood CLEC9A 1 cDCs, they stimulated CD4 1 T cells to a lesser extent than the CD1b/c 1 DCs in an MLR, cross-presented antigen and produced IL-6, TNF-a and Mip-1a.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…They expressed IRF8 and TLR3, two hallmarks of this subset in blood and spleen, 22,23 albeit at lower levels than their in vivo DC counterparts. Furthermore, similar to blood CLEC9A 1 cDCs, they stimulated CD4 1 T cells to a lesser extent than the CD1b/c 1 DCs in an MLR, cross-presented antigen and produced IL-6, TNF-a and Mip-1a.…”
Section: Discussionmentioning
confidence: 96%
“…54 Furthermore, a recent study on in vitro derived CD141 1 CLEC9A 1 DCs differentiated from HSCs in the presence of a cocktail of cytokines including SCF, Flt3L, IL-3, IL-6, GM-SCF and IL-4 has shown a similar poor response of this population to TLR stimulation with respect to IL-12p70 production. 23 They demonstrated that a further stimulus of antigenspecific T cells was required to produce IL-12p70. It may be that the cultured DCs in general, similar to mouse cultured DCs, represent an immature DC subset that requires a number of different stimuli to be fully activated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations